Two books on safeguarding harvested products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Prevention of post-harvest food losses: fruits, vegetables and root crops. A training manual, UN Food and Agriculture Organization 1989, 159pp, ISBN 92 5 102766 8 FAO Via delle Terme di Caracalla 00100 Rome ITALY